The Influence of Financial Literacy, Financial Self Efficacy, and Social Economic Status on Financial Management Behavior on Students of the Faculty of Economics, Padang State University - Satria Buana -; Dina Patrisia (Universitas Negeri Padang, 2021)
This study aims to measure the effect of financial literacy, financial self-efficacy and social economic status on the Financial Management Behavior of students at the Faculty of Economics, State University of Padang. The object in this study were active college student at the Faculty of Economics, State University of Padang with a sample of 250 respondents. Sampling was done by using the cluster random sampling technique. The criteria used are active students for the 2019/2020 school year. Data analysis used SPSS Multiple Regression Analysis. The results showed that financial literacy and financial self-efficacy had a positive and significant effect on financial management beheavior FE UNP students. Meanwhile, social economic status has no significant effect on beheavior financial management.